2000
DOI: 10.1097/00005373-200005000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Septic Complications and Multiple Organ Failure in Severely Injured Patients Is Sex Specific

Abstract: Sex influences posttraumatic morbidity in severely injured patients and supports the concept that females are immunologically better positioned toward a septic challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
152
3
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(183 citation statements)
references
References 29 publications
14
152
3
14
Order By: Relevance
“…In contrast, previous studies have found sepsis and multiple organ dysfunction to be less common in females after traumatic injuries. 32,33 Patients in our analyses who survived to 48 hr may resemble the generally critically ill population in which older women have a higher risk of ICU mortality compared with older men. 34 Finally, there was only a weak inverse correlation between nadir hemoglobin and red blood cell units transfused in the analysis of hospital mortality in 48-hr survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies have found sepsis and multiple organ dysfunction to be less common in females after traumatic injuries. 32,33 Patients in our analyses who survived to 48 hr may resemble the generally critically ill population in which older women have a higher risk of ICU mortality compared with older men. 34 Finally, there was only a weak inverse correlation between nadir hemoglobin and red blood cell units transfused in the analysis of hospital mortality in 48-hr survivors.…”
Section: Discussionmentioning
confidence: 99%
“…PCT seems to be a good marker for monitoring the status of inflammatory reaction in patients suffering from multiple trauma [12], although significant gender differences between men and women have been found [13]. Experiments have shown that hepatic tissue stimulated by TNF-alpha or Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Peak values are observed in the first 24 hours and around the 3 rd day following trauma. High levels of PCT during the first days after injury are believed to be a prognostic factor in severe systemic inflammatory response syndrome (SIRS), infection or multiple organ dysfunction syndrome (MODS) [12][13][14][15][16].…”
mentioning
confidence: 99%
“…Female sex hormones play an important role in the preservation of functionality of various organs and systems. As female rats present a better response to shock, trauma and sepsis when compared to male rats, several studies state that female hormones (estradiol, mainly) have a protective action modulating the generation of inflammatory mediators [13][14][15] . It has been shown that estrogen is also a protective factor to infections, reason why women would be more resistant than men 14 .…”
Section: Introductionmentioning
confidence: 99%
“…As female rats present a better response to shock, trauma and sepsis when compared to male rats, several studies state that female hormones (estradiol, mainly) have a protective action modulating the generation of inflammatory mediators [13][14][15] . It has been shown that estrogen is also a protective factor to infections, reason why women would be more resistant than men 14 . Furthermore, it has been demonstrated the presence of estradiol receptors (subtypes α and β) on lymphocytes, neutrophils, macrophages, dendritic cells and NK lymphocytes, suggesting that estrogens may play a role in immunocompetence regulation 16 .…”
Section: Introductionmentioning
confidence: 99%